Pertanggungjawaban Pidana Rumah Sakit dan/atau Rumah Sakit Darurat atas Kejahatan Dumping Limbah Medis Padat di Masa Pandemi Covid-19 - Dian Pertiwi Suprapto; Lia Meinda Sari; Monnachu Wemonicha Lovina (CV Rewang Rencang, 2021)
The purpose of this study is to analyze how the criminal liability of corporations in the form of hospitals and/or emergency hospitals in the event of a criminal act of Dumping solid medical waste during the Covid-19 pandemic and to identify the factors that influence the implementation of this criminal responsibility. The results of this study indicate that criminal responsibility in this case can be charged to the corporation and the management who gave the order (leader) of the criminal act. There are several factors that affect the implementation of criminal responsibility, such as the lack of optimal supervision from law enforcement officers to unclear regulations, especially for emergency hospitals, so there is a need for a renewal of legal regulations.